ANALISIS PENGAKUAN, PENGUKURAN, PENYAJIAN DAN PENGUNGKAPAN PAJAK TANGGUHAN BERDASARKAN PSAK 46 - Nurkhasanah, Nurkhasanah; Arfianti, Rizka Indri (Jurnal Akuntansi, 2024)
Discrepancies and differences in interests between accounting and taxation require companies to make fiscal corrections or adjustments between commercial financial reports and fiscal financial reports in accordance with tax regulations. The object used for this research is the financial report of PT X in 2021 - 2022, research variables are recognition, measurement, presentation and disclosure of deferred tax PSAK 46. After conducting research, regarding the analysis of the implementation of PSAK 46 deferred taxes at PT X, indicates that the recognition, measurement, presentation and disclosure of deferred tax PSAK 46 has been applied in accordance with the data in the financial statements and notes to the financial statements. The research conclusion is that the recognition of deferred tax according to PSAK 46 has been implemented by recognizing current tax and the benefits of deferred tax.